The effect of supply chain management and strategy on organizational performance through competitive advantage - Wulandari, Artha Fitri; Ernawati, Dira (Jurnal Teknika, 2024)
Rapid economic growth has intensified business competition across all industrial sectors. Companies must continuously innovate and optimize their operations to achieve a competitive advantage. Intense inter-company competition drives high market demand for products, often resulting in difficulties meeting marketing demands and suboptimal production planning. This study aims to examine how supply chain management and supply chain strategy influence company performance through competitive advantage, using PLS-SEM. The findings indicate that supply chain strategy positively affects company performance through competitive advantage, whereas supply chain management does not. Based on the hypothesis testing results, recommendations include improving effective demand management by responding quickly to demand changes, adapting to market shifts, and evaluating supply chain systems and processes. To achieve sustainable competitive advantage, companies should focus on key aspects of supply chain strategy implementation, such as increasing speed and accuracy in meeting customer demand, ensuring consistent product and service quality, and continuously evaluating and refining strategies to maintain relevance and effectiveness.